2021
DOI: 10.12659/msm.932724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes Following TiRobot-Assisted Sacroiliac Screw Fixation with Bone Grafting and Traditional Screw Fixation without Bone Grafting for Unstable Osteoporotic Sacral Fracture: A Single-Center Retrospective Study of 33 Patients

Abstract: Background This retrospective study from a single center aimed to compare patient outcomes following TiRobot-assisted sacroiliac screw fixation and bone grafting with traditional screw fixation without bone grafting in 33 patients with unstable osteoporotic sacral fracture (UOSF). Material/Methods Patients with UOSF were included and divided into 2 groups: a TiRobot-assisted surgical group with 18 patients (robot-aided sacroiliac screw fixation and bone grafting) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…According to recorded frequency of intraoperative uoroscopy, the data in this study were signi cantly decreased in the robot group (P < 0.001), which was similar to the existing reports using the same technique [16,17,24]. All guide pins in the robot group were basically successfully implanted at one time, while that in the conventional group needs to be adjusted twice or more.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…According to recorded frequency of intraoperative uoroscopy, the data in this study were signi cantly decreased in the robot group (P < 0.001), which was similar to the existing reports using the same technique [16,17,24]. All guide pins in the robot group were basically successfully implanted at one time, while that in the conventional group needs to be adjusted twice or more.…”
Section: Discussionsupporting
confidence: 85%
“…In a study of 33 osteoporosis patients with sacral fractures, the authors compared robot-aided to conventional free-hand sacroiliac screw xation. They found that robotic assistance led to higher rates of screw placement accuracy, with the robot-aided group demonstrating an accuracy of 94.4% (vs 73.3%), using accuracy criterion previously set by Gras et al [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to the uncertain entry point and the narrow bony corridor, it usually takes much time to insert the guiding wire accurately, with the consequence of excessive radiation exposure to patients and surgeons. Percutaneous fixation under the guidance of orthopedic robots has been reported with the advantages of accuracy and convenience [ 17 , 18 ]. Most important of all, robot-aided technology can also assist surgeons to plan, simulate and correct the trajectory of screws intraoperatively [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous fixation under the guidance of orthopedic robots has been reported with the advantages of accuracy and convenience [ 17 , 18 ]. Most important of all, robot-aided technology can also assist surgeons to plan, simulate and correct the trajectory of screws intraoperatively [ 17 , 18 ]. So far, the percutaneous anterior column screw fixation is possibly to be an optimal choice for the patients suffering TOAFs, especially with transverse and transverse with posterior wall fractures.…”
Section: Introductionmentioning
confidence: 99%